2021
DOI: 10.3892/etm.2021.10761
|View full text |Cite
|
Sign up to set email alerts
|

Cycloastragenol and Astragaloside IV activate telomerase and protect nucleus pulposus cells against high glucose‑induced senescence and apoptosis

Abstract: In diabetes-induced intervertebral disc degeneration (Db-IVDD), senescence and apoptosis of nucleus pulposus cells (NPCs) are major contributing factors. Telomere attrition and telomerase downregulation are some of the main reasons for senescence and eventual apoptosis. The derivatives of the Chinese herb Astragalus membranaceus , Cycloastragenol (CAG) and Astragaloside IV (AG-IV), are reportedly effective telomerase activators against telomere shortening; however, their effect in Db-IVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…At the same time, studies have found that AS IV effectively alleviated IDD in vivo and in vitro. [ 10 , 31 ] In addition, AS IV ability to stimulate the PI3K/AKT pathway has been pointed out many times and is related to antiapoptosis, antioxidative stress and the protective effect of ischemia-reperfusion. [ 32 , 33 ] However, it is not clear whether AS IV can alleviate disc degeneration by interfering with PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, studies have found that AS IV effectively alleviated IDD in vivo and in vitro. [ 10 , 31 ] In addition, AS IV ability to stimulate the PI3K/AKT pathway has been pointed out many times and is related to antiapoptosis, antioxidative stress and the protective effect of ischemia-reperfusion. [ 32 , 33 ] However, it is not clear whether AS IV can alleviate disc degeneration by interfering with PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, cycloastragenol treatment significantly increased BCL2 expression and decreased that of BAX and caspase‐3 in UC rats. Cycloastragenol can modulate BCL2/BAX/caspase‐3 in high glucose‐induced senescence 44 and brain ischaemia‐induced neuroinflammation 37 . However, no previous study has reported the effects of cycloastragenol on apoptosis in UC.…”
Section: Discussionmentioning
confidence: 99%
“…High glucose concentration is known to have adverse effects on telomerase reverse transcriptase (TERT) expression and telomere length in NPs. After treatment with CAG and AG-IV, the cell morphology and vitality significantly improve, the TERT expression of NPC and telomere length increased, and apoptosis and senescence an inhibited ( 121 ). At present, the exploration of novel pharmacotherapeutic strategies for treating IDD, particularly in the presence of concurrent diabetes, represents a highly promising avenue.…”
Section: Drug Therapy Of Diabetic Iddmentioning
confidence: 99%